Incidence and Predictors of Contrast Induced Nephropathy after Coronary Intervention at College of Medical Sciences Teaching Hospital, Bharatpur - Sharma, Sanjib Kumar; Dubey, Laxman; Laudary, Shankar; Dhungel, Sachin; Ghimire, Madhav; Pahari, Bishnu; Gautam, Samir; Guruprasad, Sogunuru; Subramanyam, Gangapatnam (Nepalese Heart Journal, 2014)
Background and Aims: The implications of radio-contrast induced nephropathyare disastrous. In Nepal there is scarcity of data on contrast induced nephropathy. This observational descriptive study was undertaken to study the incidence of contrast induced nephropathy and to identify risk factors (predictors) for the development of contrast induced nephropathy in patients undergoing coronary angiography and angioplasty in atertiary care hospital. Methods: The subject consists of 540 patients undergoing coronary intervention from 2011 to 2013 were enrolled by convenient sampling technique. Two hundreds ten patients were excluded from the study. Therefore, a total of 330 patients were studied and analyzed. Contrast induced nephropathy was defined as an increase of >25% or >0.5 mg/dl in pre-catheterization serum creatinine at or after 48 h after percutaneous coronary intervention. Estimated glomerular filtration rate as calculated by applying the 4 variables Modification of Diet in Renal Disease Study equation. Standard definitions were used to define the variables. Results: Twenty seven (8.18%) patients experienced contrast induced nephropathy. The incidence of contrast induced nephropathy in patients with baseline creatinine clearance <60 ml/min was 45.9%. Contrast induced nephropathy developed in 10% of anemic and 12.5% diabetic patients. The amount of the contrast agent administered was similar for both groups of patients (138.20±91.34ml vs. 175.56±118.86ml; p =0.254). No correlation was found between the amount of contrast agent administered and the change of serum creatinine concentration. Multivariate logistic regression analysis found that baseline e-GFR and baseline hemoglobin were independent predictors for Contrast induced nephropathy. Conclusion: The overall incidence of Contrast induced nephropathy after coronary intervention in this study is high. Patients with both preexisting renal insufficiency and anemia were at high risk of Contrast induced nephropathy. DOI: http://dx.doi.org/10.3126/njh.v11i1.10975 Nepalese Heart Journal 2014;11(1): 3-11